Description of breastfeeding success in babies aged 0-6 months born to positive COVID-19 mothers at Anwar Medika General Hospital, Sidoarjo - Valentina Febriyanti, -
Abstract According to the World Health Organization, breastfeeding is a natural way to provide nutrients that are very beneficial for the growth and development of babies. Breast milk is the best nutrition that babies need because it contains various substances and antibodies that can increase the body's immunity so it can become a protector (immune) for babies from all types of infections. During the COVID-19 pandemic, WHO and UNICEF suggest breastfeeding even if the mother is COVID-19 suspected/confirmed. The benefits of breastfeeding outweigh the risks of transmission. However, the infection prevention and control must be strictly applied when breastfeeding. This study aims to describe the success of breastfeeding in infants aged 6-12 months born to mothers positive for COVID-19. This research used a quantitative descriptive study design with a cross-sectional approach. Questionnaires were given to 76 mothers with a positive history of COVID-19. The data analysis used was univariate. The results showed that the majority (67.1%) of mothers with positive COVID-19 had received communication, information, and education (CIE) while being treated at the hospital. Most (59.2%) of COVID-19-confirmed mother unable to provide exclusive breastfeeding to their babies. Majority (89.5%) of them have implemented health protocols when breastfeeding well. There was no COVID-19 vertical transmission from mother to child during delivery or breastfeeding in 89.5% and 93.4% subjects, respectively.